Metallurgical Observation of the Buddhist Bell of Youngmoon Mountain Sangwonsa Temple - Doh, Jungmann; Park, Bangju; Lee, Jungil; Hong, Kyungtae (KOREAN INST METALS MATERIALS, 2012)
The microstructure, chemical composition, and lead isotope ratio of the Buddhist bell of Yongmoon Mountain Sangwonsa temple, which was selected as one of the three great bells of Korea by Japanese historians, were analyzed in order to estimate the origin of the material and the time of casting. The microstructure of the temple bell was composed of a copper matrix phase with alpha, a face centered cubit lattice structure, a delta phase with Cu-41 (Sn, Ag, Sb)(11) as the chemical structural formula, dispersed lead and Cu2S particles, and locally agglomerated fine particles. Through analysis of the chemical composition of the bell, a criterion (Pb: 0-3.0 wt%, Sn: 10-15 wt%) for distinguishing the bells of the Shilla dynasty from the bells of the Koryo . Chosun dynasty is proposed. Examining the lead isotope ratio of Pb-207 / Pb-206 and Pb-208 / Pb-206 of the Buddhist bell of Sangwonsa temple proved that the bell was fabricated using raw materials in South Korea, which led to the conclusion that the bell was cast in Korea and the top board of the bell has been damaged by an unknown individual. The criteria of distinguishing the bells from the Shilla dynasty from the bells of the Koryo . Chosun dynasty presented for the first time in this research is expected to aid in identifying and estimating the previously unclear production years of other bells.